“Why is this relevant for me?”: increasing content relevance enhances student motivation and vitality - Johansen, Marius Ole; Eliassen, Sigrunn; Jeno, Lucas Matias (Frontiers in Psychology, 2023)
The notion that motivation is imperative for students' psychological well-being and academic functioning is central to Self-Determination Theory (SDT). According to SDT, different types of motivations can co-occur to a various degree with separate outcomes, depending on the extent of experienced degree of autonomy. In the current study, we investigate how making a learning exercise more relevant for higher education STEM students can affect aspects of student functioning mediated through motivation. In a randomized experiment, results indicate that the students who received a more "relevant" assignment (experimental group) experienced more autonomous forms of motivation relative to the students who received a "generic" or "traditional" exercise (control group). Further, the experimental group reported higher levels of vitality and effort relative to the control group. Using a pre-and post-test design measuring changes in emotional affect during the learning activity, we found that the control group reported an increase in negative affect and a decrease in positive affect. Finally, path analysis showed significant relationships between the type of assignment provided and motivation and student functioning.